AN APPLICATION OF GENETIC ALGORITHMS TO IDENTIFY DAMAGE IN ELASTIC STRUCTURES - Mares, C; Surace, C (Journal of sound and vibration, 1996)
A technique currently under development for the detection of macroscopic structural damage in elastic structures is described. The location and quantification of the extent of the damage in elastic structures is described. The location and quantification of the extent of the damage is performed with genetic algorithms implemented by using the residual force method which is based on conventional modal analysis theory. A brief survey of the literature published on the subject, the theory of genetic algorithms and the residual forces method are included and a new formulation of an objective function for the genetic search optimization procedure is presented. The results of test cases are included in order to illustrate the techniques presented. In these examples, experimental data were simulated numerically by using finite element models of structural systems and, as demonstrated, it has been possible to identify the damage introduced to a reasonable level of accuracy.